A study on functional outcome of posterior cruciate ligament substituted total knee arthroplasty - Reddy, K. Vijaya Bhaskar; Chary, N. Brahma; Sumanth, Birru (International Journal of Research in Orthopaedics, 2021)
Background: Total knee replacement surgery is considered as a treatment of choice in patients with advanced arthritis, especially in patients where conservative treatment has been failed. Total knee replacement gives good pain relief, functional improvement of knee and correction of deformity. Methods: This is study of 39 patients following total knee arthroplasty, who were operated between August 2017 and March 2020 at MNR Medical College and Hospital, Sangareddy. They were followed up for a minimum period of 1 year and evaluated using oxford knee scoring system. Oxford knee score is designed specifically for measuring outcomes in knee arthroplasty. There were 14 right knees, 10 left knees, 15 bilateral knees. Results: There was a significant functional improvement of knee in patients and we had achieved excellent results, out of 39 patients and 4 patients had post op suprapatellar fullness, which was relieved with medications for 3 weeks and 2 patients (2 knees) without no signs of immediate post-operative period, developed infection after 6 months followed which underwent staged revision total knee replacement. The outcome categories based on oxford knee scoring system: excellent (40-48), good (30-39), fair (20-29) and poor (0-19). Conclusions: It is difficult to balance the knee with retention of posterior cruciate ligament, whereas posterior cruciate ligament substituting total knee replacement gives reproducible and good results, hence it is the preferred mode of management.